Qualitative precursory pattern before several strong earthquakes in Greece. - Baskoutas, I.; Papadopoulos, G. (Bulletin of the Geological Society of Greece, 2013)
The temporal variation of the seismicity, based on the analysis of three seismic parameters i.e., number of earthquakes, b-value and energy released, were investigated before several strong earthquakes occurrence in Greece the time period 2000-2008. The seismic parameters estimates were obtained by the means of new tool, suited to analyze earthquake catalogue, and visualize their spatio-temporal variation behaviour. The seismic data used were taken from the earthquake catalogue of the Geodynamic Institute of National Observatory of Athens, Greece. The obtained temporal variation series shows significant changes around their relative mean values, which specific phases can be related to the strong earthquakes preparation stages. This relation shows remarkable temporal regularity so that it can be establish considered as a precursor seismicity pattern. These results suggest that identification of this behaviour, by the continuous monitoring of the temporal variation of the seismic parameters, can contribute to the assessment of the current seismic hazard and to the impending strong earthquake parameters evaluation, in a given area.